2016
DOI: 10.1371/journal.pone.0161596
|View full text |Cite
|
Sign up to set email alerts
|

The Envelope Cytoplasmic Tail of HIV-1 Subtype C Contributes to Poor Replication Capacity through Low Viral Infectivity and Cell-to-Cell Transmission

Abstract: The cytoplasmic tail (gp41CT) of the HIV-1 envelope (Env) mediates Env incorporation into virions and regulates Env intracellular trafficking. Little is known about the functional impact of variability in this domain. To address this issue, we compared the replication of recombinant virus pairs carrying the full Env (Env viruses) or the Env ectodomain fused to the gp41CT of NL4.3 (EnvEC viruses) (12 subtype C and 10 subtype B pairs) in primary CD4+ T-cells and monocyte-derived-macrophages (MDMs). In CD4+ T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…In addition, mice with severe combined immunodeficiency (SCID) injected with subtype C HIV-1–infected macrophages exhibited less cognitive deficits and brain pathology than those infected with subtype B HIV-1 ( 57 ). Furthermore, subtype C HIV-1 was found to have slower replication kinetics in monocyte-derived macrophages, resulting in lower levels of macrophage-mediated neurotoxicity in vitro ( 58 ). These investigations suggest subtype C HIV-1 differentially accesses the CNS parenchyma in comparison with subtype B, indicating that the brain is an unfavorable or inaccessible reservoir site for subtype C HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice with severe combined immunodeficiency (SCID) injected with subtype C HIV-1–infected macrophages exhibited less cognitive deficits and brain pathology than those infected with subtype B HIV-1 ( 57 ). Furthermore, subtype C HIV-1 was found to have slower replication kinetics in monocyte-derived macrophages, resulting in lower levels of macrophage-mediated neurotoxicity in vitro ( 58 ). These investigations suggest subtype C HIV-1 differentially accesses the CNS parenchyma in comparison with subtype B, indicating that the brain is an unfavorable or inaccessible reservoir site for subtype C HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that a smaller V1V2 region with less glycosylation can enhance HIV-1 fusion for subtype C viruses on both CD4 T-cells and macrophage [9]. A more recent study has indicated that genetic variations within the subtype C gp41 molecule can impede HIV-1 entry and replication within CD4 T-cells and modulate cell-to-cell transmission but not in macrophages [10]. The results are interpreted that subtype specific Env incorporation within viral membranes can be subtype specific.…”
mentioning
confidence: 99%